DETERMINAN MANAJEMEN LABA DENGAN KUALITAS AUDIT SEBAGAI MODERASI PADA PERUSAHAAN DAGANG DI INDONESIA - Angela Rusdikartini P.; Ishak Ramli; MF Djeni Indrajati (Jurnal Kontemporer Akuntansi, 2023)
This study aims to examine and examine why good corporate governance (GCG), financial distress, and tax avoidance affect earnings management with audit quality as a moderating variable. The population of this study are trading companies listed on the Indonesia Stock Exchange during the 2016-2020 period with a total of 270 companies. Based on the research limits set, 173 companies were selected as research samples. Hypothesis testing using Partial Least Square path analysis with SmartPLS 3.2.9 software. The results of this study indicate that the variable of good corporate governance (GCG) affects earnings management negatively and not significantly, financial distress affects earnings management positively and significantly, tax avoidance affects earnings management positively and not significantly with the measurement of the book-tax difference. Company audit quality moderates the effect of good corporate governance (GCG) positively and not significantly, company audit quality moderates the effect of financial distress positively and significantly on earnings management, corporate audit quality moderates the effect of tax avoidance negatively and insignificantly on earnings management.